Systematics and biogeography of Anoura cultrata (Mammalia, Chiroptera, Phyllostomidae): a morphometric, niche modeling, and genetic perspective, with a taxonomic reappraisal of the genus - Molinari, Jesús; Gutiérrez, Eliécer E.; Lim, Burton K. (Zootaxa, 2023)
The nectar-feeding bats of the genus Anoura are widely distributed in the Neotropics, but are most speciose in the Andes. Anoura cultrata is a rare mid-elevation bat occurring in South and Central America. It is thought to be one of the few bat species exemplifying a latitudinal cline in body size. We address three systematic and biogeographic questions: 1) is the geographic variation in A. cultrata continuous, as argued to justify its current monotypic status? 2) do ecogeographic barriers to dispersal affect such variation? and 3) how do the genetic divergence and biogeography of the species compare to those of other members of the genus? To answer these questions, we used morphometric analyses, ecological niche modeling, and DNA barcoding. We divided the samples of A. cultrata into six geographic groups, delimited by topographic depressions separating mountain systems. We did not find significant correlations between body size and the geographic coordinates within five groups. Therefore, we conclude that ecogeographic barriers to dispersal between the regions occupied by such groups influenced morphometric variation in A. cultrata, and that despite its general north to south reduction in body size, the species does not show continuous clinal variation. A recent phylogenetic study of the genus Anoura concluded that it contains seven valid species. Our DNA barcoding analysis and morphological examination indicated that at least 10 species should be recognized, including A. peruana distinct from A. geoffroyi, and A. aequatoris and A. luismanueli distinct from A. caudifer. Moreover, we show that Central and South American populations of A. cultrata differ from each other at least at the subspecific level, thus we respectively refer to them as A. cultrata cultrata and as A. c. brevirostrum. Similarly, we refer to Central American and Mexican populations of ‘A. geoffroyi’ as A. peruana lasiopyga, and to their South American counterparts as A. p. peruana. The range of the latter subspecies reaches northeastern Venezuela. The Andes from southern Colombia to northern Peru appear to be the ancestral range of the genus.